Study on the protective effects of danshen-honghua herb pair (DHHP) on myocardial ischaemia/reperfusion injury (MIRI) and potential mechanisms based on apoptosis and mitochondria - Jiqing Bai; Xiaoping Wang; Shaobing Du; Pengfei Wang; Yaheng Wang; Lina Quan; Yundong Xie (Taylor & Francis Group, 2021)
Context Danshen, the dried root and rhizome of Salvia miltiorrhiza Bunge (Labiatae) and honghua, the dried flower of Carthamus tinctorius L. (Compositae) as the herb pair was used to treat cardiovascular diseases (CVD). Objective To study the effects of DHHP on MIRI and mechanisms based on apoptosis and mitochondria. Materials and Methods 36 SD rats (n = 6) were randomly divided into control group (Con), the ischaemia-reperfusion group (IR), positive control (Xinning tablets, XNT, 1 g/kg/d) and DHHP (1.2, 2.4, and 4.8 g/kg/d). Except for Con, the other groups were intragastrically administrated for 5 d, the rat hearts were isolated to establish the MIRI model in vitro for evaluating the effects of DHHP on MIRI. 24 SD rats (n = 6) were randomly divided into Con, IR, DPPH2.4 (2.4 g/kg/d) and DPPH 2.4 + Atractyloside (ATR) (2.4 + 5 mg/kg/d), administered intragastrically for 5 d, then treated with ATR (5 mg/kg/d) by intraperitoneal injection in DPPH2.4 + ATR group, took rat hearts to establish MIRI model in vitro for revealing mechanism. Results Myocardial infarct sizes were, respectively, 0.35%, 40.09%, 15.84%, 30.13%, concentrations of NAD+ (nmol/gw/w) were 144, 83, 119, and 88, respectively, in Con, IR, DHHP2.4, DHHP2.4 + ATR group. Cleaved caspase-3 were 0.3, 1.6, 0.5 and 1.3% and cleaved caspase-9 were 0.2, 1.1, 0.4 and 0.8%, respectively, in Con, IR, DHHP2.4 and DHHP2.4 + ATR group. The beneficial effects of DHHP on MIRI were reversed by ATR. Conclusions The improvement of MIRI by DHHP may be involved in inhibiting MPTP opening, decreasing oxidative damage, alleviating ischaemic injury and inhibiting cardiomyocyte apoptosis.